Analisis Statistik Produksi Padi di Provinsi Sumatera Utara Periode 2020-2024 - Mahara Sintong; Muhammad Miftahurridlo; Rohil Al Azizah; Chairullah Chairullah; Nadya Nadya; Maulia Maulia; Monita Monita; Malika Malika; Glen Glen (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
This study aims to analyze the development and trends in rice production in North Sumatra Province during the period 2020–2024 using a descriptive statistical approach. The data used is secondary data from the Central Statistics Agency (BPS) in the form of rice production, harvest area, and productivity. The results of the analysis show that rice production fluctuated but tended to increase, with the highest production in 2024 at 2,204,875.51 tons and the lowest in 2021 at 2,004,142.51 tons. Trend analysis produced a positive slope value of 32,861 tons per year, indicating a long-term upward trend in production. The correlation between harvest area and production shows a strong positive relationship, where an increase in harvest area is consistently followed by an increase in production. Factors affecting production fluctuations include climate change, land area, cropping patterns, and agricultural infrastructure and policy support. Overall, the results of the study confirm that increases in rice production are highly dependent on land management, productivity, and the stability of climatic conditions in the North Sumatra region.